Efektivitas Komunikasi Persuasif Pustakawan dan Komunikasi Pemasaran Perpustakaan Unimed terhadap Kepuasan Pengguna - Tessa Simahate (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2015)
This research conducted in the State University of Medan, aims at under-standing : 1) the process of persuasive communication acted by librarian; 2) effectivity of marketing communication which is implemented by the library; 3) the library users satisfaction rate to the library services; 4) effectivity of persuasive communcation and marketing communcation to the user satis-faction. By using theory of marketing communication and theory of persua-sive communication, the fact findings being analyzed. The populatio of the research is all of registered members of the Unimed’s Library. Based on the adminstration data of the Library, its members amount 19,791. The sampel of the research number 392 of the population, which are selected by technique of purposive sampling. The result of the research represents that persuasive communication by librarian and marketing communication of Unimed’s Lib-rary positively impact to the users satisfaction of the Library.